Ascophyllum nodosum seaweed extract and mineral nitrogen in Alibertia edulis seedlings - Rodrigo da S. Bernardes; Silvia C. Santos; Cleberton C. Santos; Diego M. Heid; Maria do C. Vieira; Elissandra P. Torales (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Physiological and nutritional management is an important practice for obtaining high quality seedlings. The use of seaweed extract has emerged as an alternative to fertilizers and biostimulants, although information on this with respect to Alibertia edulis, a fruit-bearing species native to the Cerrado region, is scarce. The aim of this study was to evaluate the effects of the Ascophyllum nodosum L. seaweed extract (ANE), both with and without the addition of mineral nitrogen, on the growth, nitrogen nutrient efficiency indices, and quality of A. edulis seedlings. The seedlings received five doses of ANE (0, 5, 10, 15, and 20 mL L-1 of water) via foliar application, with and without the addition of mineral N to the soil (50 mg kg-1 of urea). A randomized block design was used with the treatments arranged in a 5 × 2 factorial scheme. The plant height, stem diameter, chlorophyll index, and number of leaves obtained were analyzed in split-plots over time. Foliar application of 15 and 20 mL L-1 of ANE contributed to greater growth and seedling quality, regardless of the addition of mineral nitrogen. Seedlings treated with mineral N alongside 13.98 mL L-1 of ANE showed the greatest leaf area. The highest N use efficiency, N uptake, and nutrient use occurred in seedlings that received A. nodosum extract.